CHARACTERISTICS OF NATA FROM CARICA (Carica Pubescens) EXTRACT WITH DIFFERENT CONCENTRATION OF ACETOBACTER XYLINUM AND FERMENTATION TIME - Suryanti, Anik; Nurdyansyah, Fafa; Muliani Dwi Ujianti, Rizky; Muflihati, Iffah; Nurcholis, Mochamad (Jurnal Pangan dan Agroindustri, 2024)
Nata de carica is a product of the innovation of fermentation of carica fruit (Carica pubescens) with the use of Acetobacter xylinum as a culture. The objective of this study was to analyze the impact of Acetobacter xylinum starter concentrations and fermentation time on the physical characteristics (chewiness, color, thickness, yield), chemical (crude fiber content, water content) and organoleptic (descriptive test) of nata de carica. The experimental design was used factorial design with two factors, Acetobacter xylinum starter concentration (10%, 15% and 20%) and fermentation time (7 days and 14 days). The results showed that there was a relationship between thickness, yield, chewiness and crude fiber, the thicker the nata, the greater the yield, chewiness and crude fiber. The best results of nata de carica treatment was treatment with 20% Acetobacter xylinum concentration and 14 days of fermentation time with a thickness value of 6.29 mm, a yield value of 41.04%, a texture value (efficiency) of 521.27 g/mm, crude fiber value of 1.05%, a color value of L* 50.36, a value of a*-1.87, a b* -3.93 and water content of 98.86%. The results of the research can be concluded that the starter concentration and the fermentation time influence the physical and chemical properties of the nata de carica produced.